The Diverse Search for Synthetic, Semisynthetic and Natural Product Antibiotics From the 1940s and Up to 1960 Exemplified by a Small Pharmaceutical Player - Leisner, Jørgen J. (Frontiers in Microbiology, 2020)
This article describe screening and R&D of synthetic, semisynthetic and natural product antibiotics by a Danish pharmaceutical company, LEO Pharma during the 1940s and 1950s. LEO adopted a strategy searching for synthetic and semisynthetic antibiotics towards specific bacterial pathogens, in particular Mycobacterium tuberculosis that lead to discovery of new derivatives but no new lead compounds. On the other hand, work on natural product antibiotics led initially to no new compounds but were concluded with the serendipitously discovery of fusidic acid towards Staphylococcus aureus in 1960. The discovery process depended on the scientific challenge and included a number of contemporary approaches including open innovation; targeting specific pathogens and/or specific organs in the patient; examining the effects of antimicrobial compounds on bacterial virulence as well as on antibiotic resistant variants; and searching for antibiotic producers among microorganisms not previously well explored. These strategies were promoted by collaboration with a renowned Danish clinical microbiologist as well as company expertise in fermentation technologies, purification of bioactive compounds from organic materials and chemical synthesis.